Mengoptimalkan Personal Hygiene Kelompok Anak Usia Sekolah Suku Anak Dalam Untuk Meningkatkan Derajat Kesehatan Di Desa Bukit Suban - Dinda Oktafia; Danu Pendawa; Rakhe Maihanda; Siti Mashirotul Khoiriyah; Siska Septiani; Asparian Asparian (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Personal hygiene is one solution to minimize the risk of being contaminated with disease which aims to prevent disease in oneself and others, both physically and psychologically. The implementation of personal hygiene in the Suku Anak Dalam is still very minimal, so there is a risk of contracting non-communicable diseases such as diarrhea, malaria, intestinal worms, and hepatitis B. The absence of significant changes in health behavior from year to year has an impact on increasing morbidity rates in the Suku Anak Dalam. Therefore, assistance and empowerment are needed in optimizing personal hygiene gradually and sustainably due to characteristics, lifestyle, and lack of knowledge so that it is difficult to implement clean and healthy living behaviors. The target of this activity is the Suku Anak Dalam school age group in Bukit Suban Village, Air Hitam District, Sarolangun Regency, Jambi Province. The methods used in personal hygiene activities are brainstorming, role playing, health education, and the Movement to Embrace the Dreams and Aspirations of the Children Within (GEMPITA SAD). From this activity there was an increase in personal hygiene knowledge obtained from the pre-test and post-test with the results of 27.5% to 60% of the Suku Anak Dalam school age children who already knew about personal hygiene and could practice it properly and correctly.